INTERNATIONAL LEGAL PROTECTION OF RARE AND ENDANGERED PLANT SPECIES IN UZBEKISTAN - Babomirzaev Moumunjan Ergashovich (International Scientific and Current Research Conferences, 2023)
The article is devoted to the analysis of the international legal protection of rare and endangered plant species in Uzbekistan. The author explores the role and importance of international norms and agreements in ensuring the conservation of biodiversity in a given country, especially taking into account the threats associated with climate change, anthropogenic activities and illegal trade in rare plants. The article discusses the main documents regulating plant protection issues, such as the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and the Convention on Biological Diversity (CBD). The author also analyzes the effectiveness of national legislative and organizational measures to implement these international agreements in the context of the Uzbek environment. The article highlights the challenges faced by Uzbekistan in the field of protection of rare plants, and offers practical recommendations for strengthening the mechanisms of international legal protection for the sustainable management of biodiversity. The author calls for strengthening efforts in the field of international cooperation and exchange of experience to achieve sustainable development and preserve the unique flora of Uzbekistan in the face of global challenges.